RIOK3-Mediated Akt phosphorylation facilitates synergistic replication of Marek's disease and reticuloendotheliosis viruses. Issue 1 (31st December 2022) - Du, Xusheng; Zhou, Defang; Zhou, Jing; Xue, Jingwen; Cheng, Ziqiang
ABSTRACT: Co-infection of Marek's disease virus (MDV) and reticuloendotheliosis virus (REV) synergistically drives disease progression, yet little is known about the mechanism of the synergism. Here, we found that co-infection of REV and MDV increased their replication via the RIOK3-Akt pathway. Initially, we noticed that the viral titres of MDV and REV significantly increased in REV and MDV co-infected cells compared with single-infected cells. Furthermore, tandem mass tag peptide labelling coupled with LC/MS analysis showed that Akt was upregulated in REV and MDV co-infected cells. Overexpression of Akt promoted synergistic replication of MDV and REV. Conversely, inhibition of Akt suppressed synergistic replication of MDV and REV. However, PI3K inhibition did not affect synergistic replication of MDV and REV, suggesting that the PI3K/Akt pathway is not involved in the synergism of MDV and REV. In addition, we revealed that RIOK3 was recruited to regulate Akt in REV and MDV co-infected cells. Moreover, wild-type RIOK3, but not kinase-dead RIOK3, mediated Akt phosphorylation and promoted synergistic replication of MDV and REV. Our results illustrate that MDV and REV activated a novel RIOK3-Akt signalling pathway to facilitate their synergistic replication.